2019
DOI: 10.1136/bmjinnov-2018-000336
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating patient attitudes and barriers towards smart technology for cardiac monitoring: results from a prospective multicentre study

Abstract: ObjectivesRemote assessment of heart rate and rhythm using smart technology (ST) holds promise in screening and monitoring of atrial fibrillation (AF). However, patient engagement is paramount to the success of ST interventions.MethodsWe assessed the attitudes and potential barriers towards ST for arrhythmia monitoring in an elderly, multimorbidity cohort. Consecutive inpatients were recruited across three hospitals and administered a standardised survey regarding attitudes towards ST for arrhythmia detection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Additionally, there is limited empirical evidence regarding attitudes toward technology among patients with AF. Koshy et al [ 14 ] assessed the attitudes of patients with arrhythmias (primarily AF or atrial flutter) toward self-monitoring mobile or wearable technology and found approximately 70% were interested in the technology but reported its complexity as a limiting factor, a finding that may reflect low self-efficacy. Similarly, a qualitative study of perceptions and attitudes of patients with AF toward e-tool self-care technology found that patients’ reluctance was related to unfamiliarity with the technology; lack of ownership of certain technology (smartphone and tablet); perceptions of e-tools being complicated, impractical, and difficult to learn; and literacy challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is limited empirical evidence regarding attitudes toward technology among patients with AF. Koshy et al [ 14 ] assessed the attitudes of patients with arrhythmias (primarily AF or atrial flutter) toward self-monitoring mobile or wearable technology and found approximately 70% were interested in the technology but reported its complexity as a limiting factor, a finding that may reflect low self-efficacy. Similarly, a qualitative study of perceptions and attitudes of patients with AF toward e-tool self-care technology found that patients’ reluctance was related to unfamiliarity with the technology; lack of ownership of certain technology (smartphone and tablet); perceptions of e-tools being complicated, impractical, and difficult to learn; and literacy challenges.…”
Section: Introductionmentioning
confidence: 99%